The relationship between dietary patterns derived from inflammation and cognitive impairment in patients undergoing hemodialysis - Zhuang, Yan; Wang, Xinmei; Zhang, Xuanrui; Fang, Qian; Zhang, Xinyi; Song, Yan (Frontiers in Nutrition, 2023)
Introduction Dietary patterns were shown to be closely related to inflammation, which was independently associated with cognitive impairment (CI) in patients undergoing hemodialysis (HD). However, it remains unclear the influence of dietary patterns derived from inflammation on CI in this population. This study aimed to examine the association between dietary patterns derived from C-reactive protein (CRP) and interleukin-6 (IL-6) and CI in patients undergoing HD. Methods Dietary intake was obtained from the simplified quantitative food frequency questionnaire. Reduced rank regression (RRR) was used to extract two dietary patterns, with IL-6 and CRP as response variables. Cognitive function was examined by the Montreal Cognitive Assessment (Beijing version). Venous blood was drawn for measuring IL-6 and CRP levels. Multivariable logistic regression was used to investigate the association between dietary patterns and CI. Results Dietary pattern derived from IL-6 was not significantly associated with CI. The third quartile of dietary pattern, which used CRP as the response variable, significantly contributed to the increased risk of CI (AOR 8.62, 95% CI 1.47–50.67) after controlling age, sex, education level, marital status, and residential pattern (p-for-trend = 0.028). After considering hypertension and diabetes, physical activity level, anxiety and depression, smoking and drinking status, social support, energy intake, and the dietary pattern derived from IL-6 (p-for-trend = 0.026), the relationship between the dietary pattern derived from CRP and CI remained significant (AOR 14.54, 95% CI 1.40–151.13). Conclusion Dietary pattern associated with high CRP level, including high intake of rice, liquor, fruit, tea and coffee and low intake of dark vegetables and juice, contributed to the increased risk of CI. The association between the consumption of seafood, sweet beverages, and alcohol and CI is yet to be established. However, they may be dietary contributing factors to inflammation in patients undergoing HD.